Pengaruh Implementasi PP No. 55 Tahun 2022, Pemahaman Perpajakan Dan Modernisasi Sistem Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM - Atichasari, Anna Sofia; Ristiyana, Rida; Handayani, Sri (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to determine the effect of the implementation of PP No. 55 year 2022, understanding of taxation and modernization of the tax administration system for MSME taxpayer compliance with financial conditions as a moderatng variable. The type of research used in this research is quantitative research using primary data through questonnaires. The population of this study is MSME taxpayers who finance at BSI KCP Tangerang Cikupa. the sampling technique used purposive sampling, with a total sample of 450 respondents. Data analysis method using partial least square (PLS), using SmartPLS 3 software. Research results simultaneously implementation of PP No. 55 of 2022, understanding of taxation and modernization of the taz administration system for MSME taxpayer compliance. The results of the partial implementation of PP No. 55 of 2022 has no effect on MSME taxpayer compliance, while understanding of taxation, modernization of tax administration and financial conditions has a positive and significant effect on MSME taxpayer compliance. The tst results with the moderating variable show that financial conditions do not strengthen the effect of implementation PP No. 55 of 2022, understanding of taxation and modernization of the tax administration system for MSME taxpayer compliance.